Theoretical fundamentals of training future teachers to work in the modern inclusive environment - Kapustina О. (Problems of Engineer-Pedagogical Education, 2023)
The article considers the theoretical aspects of training future teachers in a modern inclusive environment. It is established that the state pays considerable attention to the development of ideas of inclusion, and the main provisions are highlighted in regulations. Addressing the challenges of inclusive education requires teachers to understand the importance of introducing children with special educational needs into the ordinary educational process, have a high level of vocational training, desire for selfimprovement and self-development, morality of a teacher, an educator. The article presents an analysis of scientific sources on inclusive education, which found that the concept of "inclusion" can be understood, on the one hand, as taking into account the self-worth, diversity of the child's personality, individuality and features, and, on the other hand, as "inclusion" of children with special needs into the regular educational process of education institutions. The main approaches to inclusive education are also considered, in particular, the implementation of affordable education, positive perception of individual characteristics, active participation in the educational process, overcoming obstacles and shortcomings. The leading characteristics of inclusive education are considered. The article highlights the importance of introducing the concept of "children with special educational needs", which is to understand the uniqueness of children, shifting the emphasis from the shortcomings and violations to the responsibility of society to identify and meet these needs. The author concludes that the state of inclusive education in Ukraine reflects innovative processes that allow everyone who wants to learn. This process has a positive impact on education in general and on every student and teacher in particular, which contributes to humanization and democratization. As a result of scientific research, it is established that the main requirements for training future teachers to work with children with special educational needs are the ability to introspect and desire to work with all children, taking into account their characteristics, the implementation of individual approach; availability of knowledge about modern innovative technologies and the ability to apply them in work; self-development skills; ability to interact with parents; the presence of a strong system of values and moral beliefs.